Regulator of Dust and Coal Burner of Power Boilers - W. Wujcik; T. Golec; A. Kotyra; М. Kalita; A. Smoliaz (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2004)
The papers considers problems concerning introduction of neutron regulator into engineering practice. The regulator makes it possible to regulate CO, N0^ and O2 values with the purpose to optimize ejections into environment. The paper contains scheme of automation control of cyclone dust and coal burner with the help of a neutron regulator.